THE INFLUENCE OF PERSONAL HYGIENE ELUCIDATION TO THE HAND WASHING BEHAVIOR OF SCHOOL AGED CHILDREN (STUDY AT BANJARDOWO 2 STATE ELEMENTARY SCHOOL KABUPATEN JOMBANG) - Mulyo Aji Sulistyo; Imam Fathoni; Leo Yosdimyati R (Jurnal Keperawatan, 2012)
Personal hygiene is someone’s effort to keep his or her cleaning to get physically and psychologically safety.Hand washing is one of healthy behavior, generally this behavior has been known to the children since theywere young, not only from the parents at home, and moreover it becomes children’s daily routine. Thepurpose of this research is to know the influence of personal hygiene elucidation to the hand washingbehavior of school aged children at Banjardowo 2 State Elementary school in Kabupaten Jombang.Research design is one group pre-post test. The population is 69 repondents from students in 4th, 5th, and6th grade at Banjardowo 2 State Elementary school Kabupaten Jombang with 41 respondents as a sample.Sampling used is stratified random sampling. Variable Independent is elucidation of personal hygiene.Variable Dependent is hand washing behaviour. Frequency of hand washing behaviour before elucidation isless than 21 respondents (51,2%) and hand washing behaviour after elucidation is good with 23 respondents(56,1%). From Wilcoxon test we get score p = 0,000 < α (0,05) so H1 is accepted. From the result of dataanalysis show that there is an influence between personal hygiene to the the influence of personal hygieneelucidation to the hand washing behavior of school aged children at Banjardowo 2 State Elementary schoolJombang.